PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA KEUANGAN PEMERINTAH KOTA SALATIGA DENGAN AUDIT INTERNAL SEBAGAI PEMODERASI - Eri Oktavianingsih; Maria Entina Puspita; Joko Pramono (ITB AAS Indonesia Surakarta, 2026)
This research aims to determine the effect of accountability and transparency on the financial performance of the Salatiga City government with internal audit as a partial or simultaneous moderator. The population as research objects were financial management employees in the Salatiga City Government 54 people. This research method is explanatory, while the data analysis methods used are validity test, reliability test, moderated regression analysis test, t test, f test and coefficient of determination test. The results obtained are there is a significant influence of Accountability on Financial Performance, there is a significant influence of Transparency on Financial Performance, Internal Audit moderates the relationship between Accountability and Financial Performance, Internal Audit moderates the relationship between Transparency and Performance Finance. From the F test it can be concluded that Accountability, Transparency, the interaction of Accountability with Internal Audit and the interaction of Transparency with Internal Audit simultaneously have an influence on Financial Performance. The influence of Accountability and Transparency on the Financial Performance with Internal Audit as a moderating variable is proven by the Adjusted R Square value of 71.2% which means that X1, X2 moderated by Z have a contribution on Financial Performance (Y) of 71.2%.